Dynamics of the Rayleigh-Plesset equation modelling a gas-filled bubble immersed in an incompressible fluid - Van Gorder, R (Cambridge University Press, 2016)
Temporal dynamics of gas-filled spherical bubbles are often described using the Rayleigh-Plesset equation, a special case of the Navier-Stokes equations that describes the oscillations of a spherical cavity in an infinite incompressible fluid. While analytical approximations and numerical simulations have previously been given in some parameter regimes, we are able to completely classify all possible dynamics exactly, in terms of only the model parameters. We present an analytical study of the solutions to the Rayleigh-Plesset equation in any number of spatial dimensions, and we demonstrate that the possible behaviors of solutions include bubbles of constant radius, bubbles with temporally oscillating radius, and bubbles with finite time collapse. Each of these behaviors can be predicted solely in terms of the spatial dimension, pressures acting on the bubble, and initial strain. In the case of oscillating bubbles, we give the amplitude and period of these oscillations in terms of an integral which is a function of the aforementioned parameters, while when the bubble collapses, we can similarly give the time of collapse in terms of these parameters. We give a systematic study of all possible behaviors, and capture special case solutions presented numerically or asymptotically in the literature. We also discuss the influence of both surface tension and viscosity when these terms are included in the Rayleigh-Plesset dynamics.